A cross-case study comparison of Australian metropolitan and regional cancer nurses’ experiences of work-related stressors and supports - Lauren Parkinson-Zarb; Cameron Duff; Ying Wang; Jane Mills (BMC Nursing)
Abstract Background Registered nurses are the largest single professional group working in the field of cancer care and support one of the most vulnerable patient cohorts in the healthcare system. Cancer nurses are known to experience high rates of burnout, but there are significant limitations to current research on the unique stressors experienced by this group of nurses, particularly since the emergence of COVID-19. Methods This study employs the Job Demands Resource Model (JD-R model) to better understand the experiences of Victorian cancer nurses’ work and describe factors which ameliorate burnout and work-related stress. A multiple case study research design was used in this study, with two groups of cancer nurses making up a total of 30 participants, allocated to separate cases bounded by geographical location. A two-phase study of Victorian cancer nurses in metropolitan and regional healthcare services was conducted from 2019 to 2021. Data included field notes and in-depth interviews. Data analysis used a process of elaborative coding, with a pre-conceived coding framework based on the JD-R model. A combination of thematic analysis and storyline analysis was employed to analyse the data. Results A cross-case analysis of similarities and differences identified the job demands affecting cancer nurses, and conversely, any positive job resources which may buffer these demands. Job demands identified in both cases appeared to have similar causes but were more explicitly linked to poor resourcing in the regional case. Job resources identified in both cases were similar, but it was noted how few job resources were available to buffer the many demands inherent in cancer nurses’ work. This multiple case study found that the work of cancer nurses is high in demands and low in resources. Conclusions Despite challenging work conditions, findings identified a highly engaged workforce. The job resources identified in this study suggest there are modifiable strategies to cultivate a supportive work environment for cancer nurses.